"Man plans, God laughs": Canada's national strategy for protecting critical infrastructure. (21st March 2013) - Quigley, Kevin
Abstract Critical Infrastructure Protection seeks to enhance the physical and cyber‐security of key public and private assets and mitigate the effects of natural disasters, industrial accidents and terrorist attacks. In 2009, several Canadian governments published the National Strategy and Action Plan for Critical Infrastructure (NS&AP), a framework for governments and the owners and operators of critical infrastructure – largely in the private sector – to collaborate on the security and increased resiliency of Canada's critical assets. Drawing on the social science risk literature, audits, and a three‐year research and education project, this article argues that the strategy of relationship building, collaborative risk management and information sharing is under‐developed and limited by market competition, incompatible institutional cultures, and legal, logistical and political constraints. The NS&AP should better delineate risks and identify how governments can work with industry, and acknowledge the paradox between trust and transparency, the role of small‐ and medium‐sized enterprise, and how risk management processes can vary.